360-degree Evaluation of Postgraduate residents at Rawalpindi Medical University: Appraising the achievement of core competencies by comparing the scores of 1st & - Shahid, Rizwana; Kahlid, Rabbia; Umar, Muhammad; Khan, Sadia (Journal of Rawalpindi Medical College, 2023)
Objectives: To compare 360-degree evaluation scores of postgraduate residents during 1st and 2nd cycles of evaluation to analyze the acquisition of core competencies. Materials & Methods: A cross-sectional analytical study was done to compare the acquisition of core competencies as per ACGME by MS/MD residents in 3 public sector teaching hospitals of Rawalpindi. The enrolled residents undergone 1st and 2nd cycle of 360-degree evaluation from Jan-June 2018 and July 2018 -Jan 2019 respectively. The data was gathered from supervisors, faculty, nursing staff, patients and their attendants by structured proforma. Data was analyzed by SPSS version 25.0. Specialty-wise scores were statistically presented with 95% CI. Differences in scores of core competencies during both cycles were determined by independent sample t-test. P < 0.05 was considered significant. Results: About 93 and 113 trainees were evaluated during 1st and 2nd cycle of evaluation respectively. Most (41.70%) of them were 1st year residents. 2nd cycle of evaluation revealed statistically significant improvement (P<0.00001) in all 6 core competencies. Feedback from the patients also illustrated significant difference in scores of both cycles (P = 0.01). Trainees of MS Surgery & Allied programs were determined as highly competent with 250.06 ± 38.57 score followed by those of MD Medicine & Allied (247.59 ± 42.15) and Gynecology & Obstetrics (246.71 ± 46.26) out of total score of 331. Residents of HFH and DHQ Hospital had statistically significant enhancement of competencies (P<0.0001) than those of BBH (P=0.003). Conclusion: There was substantial enhancement of core competencies among postgraduate trainees.